2000
DOI: 10.1063/1.1289799
|View full text |Cite
|
Sign up to set email alerts
|

2.12 μm InGaAs–InGaAlAs–InP diode lasers grown in solid-source molecular-beam epitaxy

Abstract: We have fabricated InGaAs–InGaAlAs–InP strained quantum well lasers with wavelength as long as 2.12 μm in solid-source molecular-beam epitaxy. A continuous-wave threshold current density of 780 A/cm2 at room temperature and a characteristic temperature of 48 K have been achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…For wavelengths below 2 mm a homogenous indium composition is chosen for the quantum wells [6]. However, calculations show that the emission wavelength of a quantum well can be significantly increased if the standard rectangular shape of the indium content within the quantum well is changed to a triangular (V-like) one, keeping the average strain constant.…”
Section: Mbe Growthmentioning
confidence: 99%
“…For wavelengths below 2 mm a homogenous indium composition is chosen for the quantum wells [6]. However, calculations show that the emission wavelength of a quantum well can be significantly increased if the standard rectangular shape of the indium content within the quantum well is changed to a triangular (V-like) one, keeping the average strain constant.…”
Section: Mbe Growthmentioning
confidence: 99%
“…The Fabry-Perot (FP) and distributed feedback buried (DFB) devices around 2.07 µm were then demonstrated by NTT's group [28][29][30][31]. After the year 2000, FP and vertical-cavity surfaceemitting lasers (VCSELs) at 2.3 µm were demonstrated by Amann et al using molecular beam epitaxy (MBE) grown InAs-containing triangular QW active region [32][33][34]. Using MOVPE grown 5 nm pure InAs as the QW layer, Mitsuhara et al in NTT's group reported FP and DFB lasers with lasing wavelength at 2.33 µm [35][36][37].…”
Section: Development Of Semiconductor Lasers In the 2-3 µM Bandmentioning
confidence: 99%
“…Compressively strained In(Ga)As quantum well (QW) structures on InP substrate offers an attractive alternative to GaSbbased materials for laser wavelength beyond 2 mm [1][2][3][4][5]. The emission wavelength can be tailored by the In composition of InGaAs QWs, whereas it is really a challenge to extend the wavelength to longer than 2.1 mm due to the significant strain [1,6].…”
Section: Introductionmentioning
confidence: 98%